Analisis Kebangkrutan dengan Model Springate S-Score pada Perbankan BUMN dan Perbankan BUSN Tahun 2012 – 2017 - Supriyadi Supriyadi (Universitas Batanghari Jambi, 2019)
This research aims to analyze the condition of the health level using the RGEC method and analyze the potential for bankruptcy by using the Springate S-Score model in BUMN banking and BUSN banking for the period 2012-2017. The population of this research were 4 BUMN banking companies and 4 BUSN banking companies in Indonesia registered with BI and OJK in 2012 until 2017. The method of determining the sample used in this research was purposive sampling. The method of data collection used is library research. The data analysis technique used the Kolmogorov-smirnov test and the Paired Sample T-Test. The results of the health level analysis using the RGEC method showed that there was no difference in the level of health between BUMN bankings and BUSN bankings during the 2012-2017 period. The results of the analysis of potential bankruptcy used the Springate S-Score model in BUMN bankings and BUSN bankings during the 2012-2017 period that the two banks has financial performance that has the potential to experience financial distress (FD). This is because the criteria for the S-Score value obtained from the study are less than 0.862. The Paired Sample T-Test results show that there is no significant difference between the S-Score value of BUMN banks and the S-Score value of BUSN banking.